PENGARUH LDR, NPL DAN NIM TERHADAP PROFITABILITAS BANK SWASTA DEVISA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sailal Arim; Asron Saputra (SCIENTIA JOURNAL, 2022)
This study aims to understand the effectsof the loan to debt ratio, non-performaan loan, and net interest margin on return on asets with the object of Indonesian foreign exchange private banking, the population used is the entire foreign exchange private banking sector in Indonesia, which is 28 companies with the sample used is 7 private foreign exchange banks. The research instrument used is documentary in nature and as wee as using secondaryinformation source which is obtained from the annual reports of Indonesian foreign exchange private banks. The analysis technique used is test of normallity, multicolinearity, heterocedasticity, and also multiplication of liniar regresion test which includes t tabel anc t count test, F tabel test, using SPSS 26 program. The result of the partial test on loan to debt ratio cant make any different on return on asets whither its increasing or hanging low, non-performing loans also have no effect on return on assets, while the partial test on net interest margins affecting on return on asets. The results of the simultaneous test, the three independent variables simultanously having its influence on the return on asets. The result of the coeficients of determinate, give the results of an influence of 21% on the return on asets, the remaining 79% is will and only can be affected by other variables besides said inependents variable.